Chemometric and computational structure–activity relationship analysis of Ziziphus jujuba and Nephrolepis cordifolia phenolics for antioxidant and antidiabetic potential - Anitha A․; Ponmurugan P․; Arunkumar D․; Vasantha Sakthi S․; Yamuna A․; Jeyapreethi S․ (South African Journal of Botany, 2026)

A comparative study of internal organs of silkworm species (Bombyx mori, Samia ricini, Antheraea mylitta, Antheraea assamensis) using stereo-zoom microscopy - Harshitha Prakash; Pawan Shukla; Gangavarapu Subrahmanyam; Himanshu Dubey; Rajal Debnath; K. P. Arunkumar; B. S. Harshitha; Ranjana Gautam; S. Manthira Moorthy (Zoomorphology, 2026)

Reproductive challenges in Indian dairy farming: an analysis of repeat breeding and infertility in Tamil Nadu - Thanammal Ravichandran; Garima Digdarshika; Mizeck G. G. Chagunda; Arunkumar Krishnamoorthy; P. Shanthra; Kiruthika Nallasamy; Chitra Ramasamy; Mohanamani Palanisamy (Tropical Animal Health and Production, 2026)

Strategic considerations for nutrient use efficiency in sugarcane: Physiological, molecular and genetic perspectives - V. Krishnapriya; R. Manimekalai; R. Gomathi; Van Hay Duong; R. Arunkumar; P.T. Prathima; K. Devakumar; K. Thamilarasi; H.K. Mahadeva Swamy; Amaresh; P. Govindaraj; Prasanta K. Dash (Plant Science, 2026)

Computational screening of lichen bioactive compounds as a potential antiviral agent against SARS-CoV-2 main proteases - S. Jeya Preethi; A. Yamuna; M. Arunkumar; E. Murugesh; P. Ponmurugan; P. Shanmughavel (In Silico Pharmacology, 2026)

Multi-trait index based Elucidation of drought tolerance potential of Saccharum spontaneum - T. Lakshmi Pathy; V. Vinu; R. Arunkumar; Gopalareddy Krishnappa; H. K. Mahadeva Swamy; R. Valarmathi; K. Dhanapal; Amaresh; P. Govindaraj; G. Hemaprabha; Bakshi Ram (Plant Physiology Reports, 2025)

Evaluation of stable reference genes for RT-qPCR analysis in Antheraea assamensis (Lepidoptera: Saturniidae) during pathogenic infections - Indumathi Kamatchi Balakrishnan; Himanshu Dubey; Pawan Shukla; Rajal Debnath; C. Vanitha; Gangavarapu Subrahmanyam; Manthira moorthy; Kallare P. Arunkumar; Vikram Kumar; Abhishek Singh; K. M. Ponnuvel (Molecular Biology Reports, 2025)

Exploring the physiological mechanisms and ecofriendly mitigation strategies to combat the synergistic effects of drought and high temperature stress in Setaria italica - S. Gowsiga; D. Vijayalakshmi; J. Deepika; P. Arunkumar; R. Sivakumar; U. Sivakumar; V. Yamuna (Cereal Research Communications, 2025)

Determining the efficacy of phytoconstituents of Ficus religiosa L. against dermatophytes through invitro and insilico approaches - A. Anitha; P. Ponmurugan; V. Hemamalini; D. Arunkumar (In Silico Pharmacology, 2025)

Green synthesis of silver nanoparticles using Ocimum sanctum for efficient Congo red dye removal: a response surface methodology approach - S. Murugeshwari; B. Senthil Rathi; N. Kalaiarasi; R. M. Saravana Kumar; I. Arunkumar; M. Vasanth; P. Senthil Kumar; Gayathri Rangasamy (Environmental Monitoring and Assessment, 2025)

Physiological basis and metabolite profiles of pre harvest sprouting resistance in rice varieties of Tamil Nadu - J. Deepika; D. Vijayalakshmi; Santosh Ganapati Patil; S. Vellaikumar; P. Arunkumar; V. Ravichandran; K. Thirukumaran (Cereal Research Communications, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Novel biosynthesized zinc selenite photocatalysts for enhanced degradation of oxytetracycline and Rhodamine B dye with antibacterial activity - A. Anitha; P. Ponmurugan; D. Arunkumar; C. S. Sumathi; M. Sathishkumar; T. Purushothaman (BioMetals, 2025)

First report of leaf spot disease on Zanthoxylum rhetsa caused by Fusarium solani-melongenae in India - N. Surmina Devi; T. Shantibala; Arunkumar Phurailatpam; N. Y. Chanu; Anju Choudhury; Priyanka Irungbam; P. Raja; R. C. Shakywar (Indian Phytopathology, 2025)

Contrasting gut bacteriomes unveiled between wild Antheraea assamensis Helfer (Lepidoptera: Saturniidae) and domesticated Bombyx mori L. (Lepidoptera: Bombycidae) silkworms - Gangavarapu Subrahmanyam; Yeruva Thirupathaiah; N. Vijay; Rajal Debnath; K. P. Arunkumar; Mallikarjuna Gadwala; Prashant A. Sangannavar; S. Manthira Moorthy; Mahananda Chutia (Molecular Biology Reports, 2024)

Host seaweed extracts effect on epiphytic Acrochaetium sp growth and its phycobilipigments content and biological activity - V. R. Umashree; P. Dhanya; Kulanthaiyesu Arunkumar (Vegetos, 2024)

(Re)-thinking the red seaweed biomass for biofuel production to meet sustainable development goals toward circular bioeconomy - M. P. Sudhakar; K. Arunkumar; G. Dharani; Thangavel Mathimani (Energy, Ecology and Environment, 2024)

In Vitro Plant Growth Promoting Effect of Fucoidan Fractions of Turbinaria decurrens for Seed Germination, Organogenesis, and Adventitious Root Formation in Finger Millet and Eggplant - Arya Kaniyassery; Sachin Ashok Thorat; Nagarajan Shanthi; Shashikala Tantry; M. P. Sudhakar; Kulanthaiyesu Arunkumar; Annamalai Muthusamy (Journal of Plant Growth Regulation, 2024)
Bioactive ingredients derived from brown algae have been extensively used in the food, medicine, and cosmetic industries. In this study, fucoidans of low and high molecular fractions (LMF and HMF) extracted and isolated from brown alga Turbinaria decurrens were analyzed for their efficacy on seed germination, seedling growth, callus induction, direct organogenesis, and adventitious root formation in eggplant and finger millet. The yield and sugar content of LMF were higher than HMF. FTIR confirmed that the isolated fractions containing fucoidan has more sulfate groups in HMF than in LMF. The results showed an enhanced seed germination and seedling growth in both crops. In eggplant, 1 mg/L LMF treatment showed the maximum germination (91.6%), whereas, in finger millet, 0.1 and 0.5 mg/L LMF recorded a substantial increase in germination percentage (41.6 and 46%). Maximum fresh weight (FW) was noted with 1.0 mg/L LMF, and 1.0 mg/L LMF and 0.5 mg/L HMF showed maximum dry weight (DW) in eggplant. In finger millet, maximum DW was observed in 0.5 mg/L LMF and 1.0 mg/L HMF. Maximum biomass was noted in the 0.1 mg/L LMF treated group in the case of callus growth in eggplant. Similarly, the shoot tip initiation, proliferation, and plantlet regeneration were significantly improved with fucoidan LMF (0.1 mg/L). In conclusion, fucoidan extracted from T. decurrens exhibiting natural growth promoter property is reported for the first time in this study. These fucoidan fractions, LMF and HMF, can be utilized as cost-effective supplements in plant tissue culture media replacing the commercial PGRs for micropropagation.

Performance analysis on a compression ignition engine fueled with algae, rice bran methyl esters, and their diesel blends at optimized blend proportion, injection timing and load - Jayaprabakar Jayaraman; T. Arunkumar; P. Senthil Kumar; Anish Mariadhas; Prabhu Appavu; Gayathri Rangasamy (Fuel, 2023)

Mitigating abiotic stresses using natural and modified stilbites synergizing with changes in oxidative stress markers in aquaculture - D. Arunkumar; K. K. Krishnani; Neeraj Kumar; B. Sarkar; A. K. Upadhyay; P. B. Sawant; N. K. Chadha; R. Abisha (Environmental Geochemistry and Health, 2023)

Efficacy of Eisenia bicyclis phlorotannins in the treatment of diabetes and reducing inflammation - Rathinam Raja; Shanmugam Hemaiswarya; Kulanthaiyesu Arunkumar; N. Mathiyazhagan; Sabariswaran Kandasamy; A. Arun; P. Ramasamy (Food Bioscience, 2023)

Direct, indirect, post-infection damages induced by coronavirus in the human body: an overview - Sivan Padma Priya; P. M. Sunil; Sudhir Varma; Carel Brigi; Mohammad Faruq Abd Rachman Isnadi; J. A. Jayalal; R. Arunkumar Shadamarshan; S. Suresh Kumar; Neela Vasantha Kumari; Rishi P. R. Kumar (VirusDisease, 2022)

XSP10 and SlSAMT, Fusarium wilt disease responsive genes of tomato (Solanum lycopersicum L.) express tissue specifically and interact with each other at cytoplasm in vivo - Johni Debbarma; Banashree Saikia; Dhanawantari L. Singha; Jitendra Maharana; Natarajan Velmuruagan; Hariprasanna Dekaboruah; Kallare P. Arunkumar; Channakeshavaiah Chikkaputtaiah (Physiology and Molecular Biology of Plants, 2021)

SlHyPRP1 and DEA1, the multiple stress responsive eight-cysteine motif family genes of tomato (Solanum lycopersicum L.) are expressed tissue specifically, localize and interact at cytoplasm and plasma membrane in vivo - Banashree Saikia; Johni Debbarma; Jitendra Maharana; Dhanawantari L. Singha; Natarajan Velmuruagan; Hariprasanna Dekaboruah; Kallare P. Arunkumar; Channakeshavaiah Chikkaputtaiah (Physiology and Molecular Biology of Plants, 2020)

Physiological traits imparting drought stress tolerance to promising sugarcane (Saccharum spp.) clones - R. Gomathi; V. Krishnapriya; R. Arunkumar; P. Govindaraj; Bakshi Ram (Plant Physiology Reports, 2020)

Life history, phenology, host range and natural enemies of Acria meyricki Shashank and Ramamurthy (Lepidoptera: Depressariidae): an emerging defoliator of oil palm, Elaeis guineenis Jacq. In India - L. Saravanan; P. Kalidas; T. Phanikumar; D. Dwarakakumar; Ankita Gupta; R. Arunkumar (Phytoparasitica, 2020)

Multigene CRISPR/Cas9 genome editing of hybrid proline rich proteins (HyPRPs) for sustainable multi-stress tolerance in crops: the review of a promising approach - Banashree Saikia; Sanjay Singh; Johni Debbarma; Natarajan Velmurugan; Hariprasanna Dekaboruah; Kallare P. Arunkumar; Channakeshavaiah Chikkaputtaiah (Physiology and Molecular Biology of Plants, 2020)

Genetic relatedness does not predict the queen’s successors in the primitively eusocial wasp, Ropalidia marginata - Saikat Chakraborty; Shantanu P. Shukla; K. P. Arunkumar; Javaregowda Nagaraju; Raghavendra Gadagkar (Journal of Genetics, 2018)

Erratum: The autoregulatory loop: A common mechanism of regulation ofkey sex determining genes in insects - Suresh Kumar Sawanth; Gajula Gopinath; Nagraj Sambrani; Kallare P Arunkumar (Journal of Biosciences, 2016)

Genotyping of human adenoviruses circulating in Southwest India - C. Akhil; P. G. Suresha; S. Sabeena; M. Hindol; G. Arunkumar (VirusDisease, 2016)

Pilot scale thin film plate reactors for the photocatalytic treatment of sugar refinery wastewater - S. Saran; G. Kamalraj; P. Arunkumar; S. P. Devipriya (Environmental Science and Pollution Research, 2016)

The autoregulatory loop: A common mechanism of regulation of key sex determining genes in insects - Suresh Kumar Sawanth; Gajula Gopinath; Nagraj Sambrani; Kallare P Arunkumar (Journal of Biosciences, 2016)

Drosophila intersex orthologue in the silkworm, Bombyx mori and related species - K. P. Arunkumar; J. Nagaraju (Genetica, 2011)

Quercetin downregulates matrix metalloproteinases 2 and 9 proteins expression in prostate cancer cells (PC-3) - M. R. Vijayababu; A. Arunkumar; P. Kanagaraj; P. Venkataraman; G. Krishnamoorthy; J. Arunakaran (Molecular and Cellular Biochemistry, 2006)